Is urban sprawl back on the political agenda?: local growth control, regional growth management, and politics - Leo, Christopher et al. (1998)
The author argues that the apparent ineffectuality of efforts to control urban sprawl is in some part a result of a failure to distinguish between growth controls, which have a well-earned reputation as a thinly veiled form of NIMBYism and regional growth management (RGM), which involves the attempt to set out rules for development that are designed to preserve the livability, viability, and attractiveness of an urban area as a whole. This study surveys emerging political forces favoring RGM and notes signs that a new constellation of forces is emerging. It assesses the significance of this shift. - Reproduced
Keywords: Urban development